2021
DOI: 10.2147/nss.s282869
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Obstructive Sleep Apnea Have Altered Levels of Four Cytokines Associated with Cardiovascular and Kidney Disease, but Near Normal Levels with Airways Therapy

Abstract: Introduction Obstructive sleep apnea (OSA) results in chronic intermittent hypoxia leading to systemic inflammation, increases in pro-inflammatory cytokines TNF-Alpha and IL-6, and increased risk for a number of life threatening medical disorders such as cardiovascular and kidney disease. Methods A BioPlex Array was used to examined the serum levels of four cytokines also expressed in endothelial cells and/or macrophages and associated with cardiovascular and kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Wang et al [ 24 ] demonstrated that disturbances of genioglossal mitophagy are related to IH-induced mitochondrial morphology and function impairment, and supplementation of adiponectin can relieve the impairment via enhancing mitophagy. A two-way relationship between OSA and renal dysfunction has been proven in recent years [ 1 , 2 ]. As a novel pathophysiological feature of OSA, IH was demonstrated to be closely associated with renal impairment in experimental studies [ 7 10 , 25 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [ 24 ] demonstrated that disturbances of genioglossal mitophagy are related to IH-induced mitochondrial morphology and function impairment, and supplementation of adiponectin can relieve the impairment via enhancing mitophagy. A two-way relationship between OSA and renal dysfunction has been proven in recent years [ 1 , 2 ]. As a novel pathophysiological feature of OSA, IH was demonstrated to be closely associated with renal impairment in experimental studies [ 7 10 , 25 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between obstructive sleep apnea (OSA) and renal dysfunction was found in recent years [ 1 , 2 ]. Especially, OSA can aggravate renal dysfunction in chronic renal diseases and vice versa [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A poor sleep profile or quality is another important risk factor of increasing CKDs risk (42). SA is a condition that has serious health consequences, has an increased risk of death, and is common in patients with CKDs (43,44) and DKD (45). Obstructive SA-related hypoxia causes several negative systemic effects, including oxidative stress (46,47), inflammation, and sympathetic activation, all of which contribute to the progression of renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between IH and cytokine secretion has been reported not only in relation to insulin resistance and glucose intolerance, which is reviewed in this article, but also in relation to abnormal cytokine secretion associated with cardiovascular and renal diseases, nasal mucosal injury, and inflammation of the upper respiratory tract [34][35][36][37]. Since we previously investigated the way in which IH induces impaired insulin secretion/insulin resistance in in vitro experimental systems using pancreatic β cells, neuronal cells, hepatocytes, adipocytes, skeletal muscle cells, and cardiomyocytes [5,7,19,25,32,38], in this review, we focus on how IH induces insulin resistance.…”
Section: Introductionmentioning
confidence: 99%